Career satisfaction and barriers perceived among Malaysian dentists with expanded roles at specialist clinic - Ab Malek, Azizi; Mohd Radzi, Nawwal Alwani; Che Musa, Muhd Firdaus (2022)
Public dentists interested in postgraduate studies were required to complete clinical attachments at the Ministry of Health (MOH) Dental Specialist Clinic (DSC). This cross-sectional quantitative study aimed to explore career satisfaction and barriers perceived by Malaysian dentists at MOH Malaysia's DSC. A total of 208 dentists from DSC nationwide completed an online questionnaire in June 2022. Demographic data and information on dentists' expanded roles were retrieved. Responses on dentists' satisfaction and barrier perceived were collected using a 5-point ordinal scale. The Mann-Whitney U and Kruskal Wallis Test were used to compare the mean rank differences for career satisfaction. Factors influencing career satisfaction were analysed using Multiple Logistic Regression (MLR) (p<0.05). The mean age of the respondents was 32.68 ± 2.48. Almost half (49%) of the respondents were attached to a non-hospital-based clinic. The majority (72%) of them were permanently attached to the DSC. Most dentists (50.96%) strongly agree they received no financial incentives for their expanded role at the MOH DSC. Dentists attached at a non-hospital-based clinic (p=0.046), working with more than 15 years of experience (p=0.013) and having 12 to 18 months duration of attachment (p=0.014), were more satisfied. MLR analysis revealed that non-Malay (OR=1.54; p=0.035) and those who applied for scholarships more than three times (OR=1.85; p=0.050) were more satisfied. In contrast, over 19 months at DSC decreased career satisfaction (OR=0.44; p=0.029). Despite a similar organisational structure, DSC dentists had different satisfaction levels. Dentists' ethnicity, duration of attachment, and frequency of applying for scholarships influenced their career satisfaction. Future career advancement plans in the MOH should consider these important influencing factors to ensure the delivery of quality healthcare from their personnel.